Robust PD-type iterative learning control design for uncertain batch processes subject to nonrepetitive disturbances - Maniarski, Robert; Paszke, Wojciech (1975- ); Hao, Shoulin; Tao, Hongfeng
This paper develops PD-type iterative learning control schemes for a class of uncertain batch processes subject to nonrepetitive disturbances. By means of two-dimensional/repetitive setting, the sufficient conditions for batch-to-batch error convergence and $\mathcal{H}_{∞}$ disturbance attenuation are formulated and analyzed. Subsequently, the procedure for computing the desired control law matrices is formulated in terms of solvability of linear matrix inequalities.
Keywords: iterative learning control; batch processes; robust control; nonrepetitive uncertainty